E-voting in the Village Head Election in Batanghari and Kabupaten Bogor Regencies - Apriani, Tini; Hamudy, Moh. Ilham A.; Rifki, M. S.; Hadi, Anung S. (Research and Development Agency Ministry of Home Affairs, 2018)
The manual Village Head Elections (Pilkades) by using a ballot has weaknesses that then gives rise to various problems, among them that some of the voters cast the wrong way, slow counting process, as well as abuse of the voting invitation that should be given to the legitimate prospective voters, the government is required to find the right solution to minimize some of these problems, one of which is the application of e-voting technology (electronic voting). Therefore, this study will discuss the effectiveness of e-voting in Pilkades at Batanghari and Bogor regencies, the urgency of e-voting implementation on Pilkades; as well as the urgency of the policy requiring the use of e-voting on Pilkades. The method being utilized in this study used descriptive narrative method with a qualitative approach. While the data collection techniques are using interviews and documentation. The result of the research shows that the use of e-voting can facilitate voters, faster, more efficient, transparent and accurate at the time of voting and counting, also dependable in Pilkades disputes process. Therefore, a policy that provides an opportunity for the use of e-voting method in the village head elections is required, so that the implementation of e-voting in all village head elections can be performed more effectively. E-voting is also very important amid the rapidly growing use of technology.